Didactic Issues of Formation of Professional Activity of Students - Khushnazarova Mamura Nodirovna (Researchparks Publishing, 2022)
This article is devoted to the expansion of the volume of pedagogical and psychological knowledge and the problems of the formation of professional skills of future specialists in the process of higher pedagogical education.